2013
DOI: 10.1108/mf-12-2009-0143
|View full text |Cite
|
Sign up to set email alerts
|

How bureaucracy and corruption affect economic growth and convergence in the European Union

Abstract: Purpose -This paper aims to examine the impact of corruption and bureaucracy on economic growth in Greece as measured by the growth rate of per capita GDP. Also, using the mean per capita GDP of the EU as a benchmark, it seeks to investigate the convergence timing of Greece with the EU. Design/methodology/approach -The empirical approach taken is based on beta convergence theory. Findings -The results confirm the negative impact of bureaucracy and corruption on economic growth. However, the corruption exerts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
4
13
0
3
Order By: Relevance
“…The absence of internal conflicts, ethnic tensions in the region contributed positively to growth prospects. Bureaucracy was high in the region which had an effect of retarding growth and our findings are consistent with studies by Papaconstantinou et al (2013) and Catrinescu et al (2006). The other four institutional variables did not directly affect the rate of growth in the region.…”
Section: 21institutional Variablessupporting
confidence: 82%
See 1 more Smart Citation
“…The absence of internal conflicts, ethnic tensions in the region contributed positively to growth prospects. Bureaucracy was high in the region which had an effect of retarding growth and our findings are consistent with studies by Papaconstantinou et al (2013) and Catrinescu et al (2006). The other four institutional variables did not directly affect the rate of growth in the region.…”
Section: 21institutional Variablessupporting
confidence: 82%
“…Papaconstantinou et al (2013) argues that bureaucracy together with corruption negatively affects growth but the causal relationship moves from corruption and bureaucracy to economic growth.…”
Section: 22empirical Reviewmentioning
confidence: 99%
“…There is an inverse relationship between corruption and growth and development (Atuilik, 2013;Lambsdorff, 2005;Mauro, 1998;Papaconstantinou, Tsagkanos, & Siriopoulos, 2013;Rady, 2016;Tanzi, 1998). Corruption also contributes to reducing domestic and foreign investment, due to the higher costs of entry and the uncertainties of operating in a corrupt environment (Ahmadi & Homauni, 2011;Mauro, 1998;Myint, 2000).…”
Section: Defining Corruptionmentioning
confidence: 99%
“…Freckleton, Wright, and Craigwell (2011) found that in the cases of the developing economies, lower levels of corruption enhance the impact that Foreign Direct Investment (FDI) has on economic growth. Papaconstantinou, Tsagkanos, and Siriopoulos (2013) found that corruption has a negative impact on economic growth. Seleim and Bontis (2009) explored the relationship between culture and corruption and the findings revealed that individual collective practices encourage corruption, and uncertainty avoidance increases levels of corruption.…”
Section: Literature Reviewmentioning
confidence: 99%